2016
DOI: 10.5114/pm.2016.61195
|View full text |Cite
|
Sign up to set email alerts
|

Benign metastasizing leiomyoma in triple location: lungs, parametria and appendix

Abstract: Benign metastasizing leiomyoma (BML) usually are situated in one organ, most often in lungs. BML patients typically have a history of uterine leiomyoma treated with hysterectomy, myomectomy or subtotal hysterectomy. The aim of the study was to present the case of a 53-year-old woman with triple location in the lungs, parametria and appendix. She had undergone a myomectomy 26 years earlier. In 2015, she was admitted to the surgical department because of abdominal pain, whereupon a cholecystectomy was performed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…In review study, microscopic examination of haematoxylin and eosin slides has demonstrated the characteristic features of smooth muscle cell differentiation, which was also confirmed by immunohistochemistry smooth muscle actin positivity.Additional immunohistochemistry Ki67 showed a low tumour cell proliferation index, which favors a benign behavior [ 3 , 4 , 7 , 8 , 11 14 , 17 , 18 , 20 22 , 27 , 31 37 , 41 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In review study, microscopic examination of haematoxylin and eosin slides has demonstrated the characteristic features of smooth muscle cell differentiation, which was also confirmed by immunohistochemistry smooth muscle actin positivity.Additional immunohistochemistry Ki67 showed a low tumour cell proliferation index, which favors a benign behavior [ 3 , 4 , 7 , 8 , 11 14 , 17 , 18 , 20 22 , 27 , 31 37 , 41 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study did not provide a clear answer why some uterine leiomyomas cause metastases described in some articles as benign. [14]…”
Section: Discussionmentioning
confidence: 99%
“…Some reports describe only synchronous occurrence of different types of LBU. [3,4] The case reports describe different types of LBU as an individual event in the history of the disease. [58]…”
Section: Introductionmentioning
confidence: 99%
“…Despite being histologically benign, leiomyoma has clinically malignant potential. Metastases have been reported to a number of different sites, including the spine [ 1 4 ], skull [ 1 ], rib and vertebra [ 5 ], retroperitoneum [ 6 ], parametria [ 7 ], appendix [ 7 ], lymph nodes [ 8 , 9 ], and most commonly the lung [ 10 ].…”
Section: Discussionmentioning
confidence: 99%